The importance of the correct choice of Franz diffusion cell volume for in vitro drug release testing of wound dressings: Pomen pravilne izbire volumna Franzove difuzijske celice za in vitro testiranje sproščanja zdravil pri oblogah za rane - Maver, Uroš; Maver, Tina (Acta Medico-Biotechnica, 2023)
Purpose: Wound dressings are one of the most commonly used products in wound care. Nowadays, various wound dressings are developed containing different active ingredients, often drugs from different pharmacodynamic groups. Considering the variable and changing environment in each wound type, it is important that the experimental design for evaluating the in vitro drug release of such materials takes into account these different conditions. Methods: For this purpose, Franz diffusion cells for in vitro drug release testing are the method of choice, as they are not only able to simulate different conditions during wound healing but also allow for a certain degree of possible changes in the experimental design (e.g., diffusion cell size). Results: In this study, we aimed to compare two Franz diffusion cells with different volumes of receptor medium to evaluate naproxen release from an alginate-based model wound dressing. We confirmed that the volume of the receptor medium not only affects the amount of drug released in the selected time but also significantly influences the release mechanism. Conclusion: The different volumes of the Franz diffusion cell receptor compartments allow the simulation of wounds with a higher and a lower degree of exudation. The experimental design for in vitro drug release testing based on Franz diffusion cells must be based on a thorough consideration of the targeted wound type for which the dressings are being developed.